The effect of mobile text messages on knowledge and perception towards cancer and behavioral risks among college students, Northeast Ethiopia: A randomized controlled trial protocol. - Foziya Mohammed Hussien; Anissa Mohammed Hassen; Zinet Abegaz Asfaw; Aragaw Yimer Ahmed; Hamid Yimam Hassen (PLoS ONE)
Background Cancer is an emerging public health problem in Ethiopia. A significant proportion of premature cancer deaths are preventable. The socioeconomic impact of cancer can be considerably reduced provided that effective interventions are put in place to control risk factors. Text-messaging has been currently targeted as a simple and efficient tool for providing people with health information. Objective To evaluate the effectiveness of mobile text messages in improving knowledge and perception on cancer and behavioral risks among college students. Methods Design: a single-blind, 2-arm randomized controlled trial will be used. Setting: the study will be conducted among public colleges in Dessie town, Northeast Ethiopia. Study population: students who are studying in all public colleges. Intervention: a text message related to cancer risk factors once a day for two months. Control groups will receive general health messages daily for two months. Data: Socioeconomic characteristics, health belief variables, and behavioral risk factors of cancer will be collected before and after the intervention. Text messages will be provided based on the health belief model (HBM). Primary outcomes: cancer risk knowledge score and risk perception will be measured at baseline and 6 months post-randomization. Secondary outcomes: a change in mean healthy diet score, physical activity level, alcohol intake, and tobacco use will be measured at baseline-, 3, and 6 months post-randomization. Analysis: We will compute descriptive statistics for each outcome pre and post-intervention. To test the change in knowledge and perception, paired t-test will be used. Analysis of Covariance will be used to test over group comparison. Trial registration ClinicalTrials.gov (https://register.clinicaltrials.gov) NCT04269018.